Peran Istrumen Redistribusi Syariah (Zakat, Infak, dan Wakaf) dalam Mengurangi Kesenjangan Sosial Ekonomi dan Mewujudkan Pemerataan Kesejahteraan) - Renaldi Ikhsan; Nanda Suryadi (Ummul Qura Jurnal Institut Pesantren Sunan Drajat (INSUD) Lamongan, 2026)
Socio-economic inequality remains a development challenge in Indonesia, reflected in unequal income distribution, access to education, healthcare, and economic opportunities. Statistics Indonesia reported that the country’s Gini Ratio in 2024 was 0.381, indicating that inequality remains relatively high. This study aims to analyze the role of Islamic redistributive instruments, namely zakat, infaq, and waqf, in reducing socio-economic inequality and promoting equitable welfare distribution. The study employs a qualitative approach using library research methods through a review of relevant academic journals, books, and official reports. Data were analyzed using descriptive-analytical and content analysis techniques. The findings show that zakat plays a role in income redistribution and poverty alleviation, infaq strengthens social solidarity and addresses urgent needs, while waqf contributes to the development of long-term productive assets. The integration of these three instruments has the potential to become a strategic solution in supporting sustainable welfare equality.